Perrotta individual sexual matrix questionnaire" (PSM-1). The new clinical questionnaire to investigate the main areas of the individual sexual matrix - Giulio Perrotta (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
The present work proposes the drafting of a questionnaire capable of investigating all the areas of clinical interest of individual human sexuality. By analysing the main psychosexual tests, we proceeded to draft a test that contains five sections: the first one is dedicated to personal and contact data; the second one is dedicated to sexual history; the third one is dedicated to emotional and emotional profiles; the fourth one is dedicated to functional and dysfunctional behavioural profiles in sex; finally, the fifth section is dedicated to the study of relational behaviour in the couple. A series of proposed questionnaires, initialed by the therapist during the clinical interview session, to study the patient's sexual matrix and complete his or her personality profile.